Bismuth Oxyhalides for NOx Degradation under Visible Light: The Role of the Chloride Precursor - Francesca Tessore (Catalysts, 2021)
Photocatalysis is a green technology for tackling water and air contamination. A valid alternative to the most exploited photocatalytic material, TiO2, is bismuth oxyhalides, which feature a wider bandgap energy range and use visible radiation to attain photoexcitation. Moreover, their layered structure favors the separation of photogenerated electron–hole pairs, with an enhancement in photocatalytic activity. Controlled doping of bismuth oxyhalides with metallic bismuth nanoparticles allows for further boosting of the performance of the material. In the present work, we synthesized Y%Bi-doped BiO(Cl0.875Br0.125) (Y = 0.85, 1, 2, 10) photocatalysts, using cetyltrimethylammonium bromide as the bromide source and varying the chloride source to assess the impact that both length and branching of the hydrocarbon chain might have on the framing and layering of the material. A change in the amount of the reducing agent NaBH4 allowed tuning of the percentage of metallic bismuth. After a thorough characterization (XRPD, SEM, TEM, UV-DRS, XPS), the photocatalytic activity of the catalysts was tested in the degradation of NOx under visible light, reaching a remarkable 53% conversion after 3 h of illumination for the material prepared using cetylpyridinium chloride.